ANALISIS AKUNTABILITAS PENGELOLAAN KEUANGAN DI MASJID Al-BAROKAH DI KECAMATAN JELUTUNG BERDASARKAN ISAK 35 - Rita Herawati; Khairiyani Khairiyani (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2026)
Mosque organizations are expected to present their financial reports in accordance with ISAK 35 reporting standards. The large number of mosques whose financial records are still simple can reduce the accountability of mosque financial management. The implementation of accountability can increase public trust to donate funds to the mosque. Therefore, this study aims to determine the form of accountability for financial management and financial reporting of the Al-Barokah mosque based on ISAK 35. This study was conducted using a qualitative descriptive approach. The type of research is field research, where data is obtained through observation and interviews as well as other secondary data. The object used is the Al-Barokah Mosque, Jelutung, using research subjects. This focuses on the accountability of the financial management of the Al-Barokah Mosque in the concept of trust and community participation for progress at the Al-Barokah Mosque, Jelutung District. The validity of the data uses direct data sources. The results of the findings indicate that there are two types of accountability for the management of the Al-Barokah Mosque. First, accountability to the servants of Allah as a form of accountability of the management for the trust and trust given in managing donation funds. Second, accountability to the community and congregation for the management of the Mosque by recording cash receipts and expenditures through a financial reporting information board written weekly by the Mosque treasurer. Regarding the guidelines for preparing financial reports based on ISAK 35, the Al-Barokah Mosque has never implemented the standard and only does simple bookkeeping.